A comparison between the Simplified Disease Activity Index (SDAI) and the Disease Activity Score (DAS28) as measure of response to treatment in patients undergoing different therapeutic regimens - Gabriele Valentini; Sergio Migliaresi; Giovanni La Montagna; Gabriella Molinaro; Giovanna Cuomo (PAGEPress Publications, 2011)
Objective: To compare the SDAI values to DAS28 scores in RA patients undergoing different DMARD regimens. Methods: The SDAI is an unweighted numerical sum of five outcome parameters: tender and swollen joint count (based on 28-joint assessment), patient and physician global assessment of disease activity (visual analogue scale: 0-10 cm) and level of C-reactive protein (mg/dl). 80 patients (F/M 68/12; age between 20-68 years, median 52) with active rheumatoid arthritis were prospectively enrolled in the study. The patients were randomly assigned to one of four groups according to the therapeutic regimens: group I: Methotrexate (MTX) 15 mg/weekly + salazopyrin 2 g/daily; group II: MTX 15 mg/weekly + infliximab 3 mg/Kg at time 0, 2, 4 and every 8 weeks; group III: MTX 15 mg/weekly + etanercept 25 mg/twice weekly; group IV: MTX 15 mg/weekly + adalimumab 40 mg/every other week. SDAI and DAS28 were determined at baseline and after 6 months in each patient. Mean changes in SDAI values were compared to those detected in DAS 28 at baseline and after 6 months. Results: SDAI and DAS 28 were found to be significantly correlated at baseline. Moreover, changes in SDAI over time paralleled those in DAS, and were found to be significantly correlated. Conclusions: SDAI is a valid measure of response to treatment in RA patients undergoing different therapeutic regimens.